Social contextual factors associated with lifetime HIV testing among the Tushirikiane urban refugee youth cohort in Kampala, Uganda: Cross-sectional findings. (March 2022) - Logie, Carmen H; Okumu, Moses; Berry, Isha; Loutet, Miranda; Hakiza, Robert; Kibuuka Musoke, Daniel; Mwima, Simon; Kiera, Uwase Mimy; MacNamee, Clara; Kyambadde, Peter
Background: Urban refugee youth may live in social contexts characterized by structural drivers of HIV such as poverty and violence. Knowledge gaps remain regarding HIV testing practices among urban refugee youth, despite the increasing trend toward refugee settlement in urban contexts. This study examined social contextual factors associated with lifetime HIV testing among urban refugee youth in Kampala, Uganda. Methods: We conducted a community-based study with a peer-recruited cohort of urban refugee youth aged 16–24 years living in Kampala's informal settlements, and present baseline cross-sectional findings. We conducted descriptive statistics and logistic regression to examine socio-demographic (e.g., gender and age), material (e.g., income insecurity and education), relational (e.g., social support), and symbolic contexts (e.g., HIV-related stigma and intimate partner violence (IPV]) associated with lifetime HIV testing. Results: Participants ( n = 450) had a mean age of 20.4 years (standard deviation: 2.4 years), most lived in Uganda for 1–5 years (53.2%), and less than half reported lifetime HIV testing (43.4%). In multivariable analyses, odds of lifetime HIV testing were higher among youth with secondary school education or higher (adjusted odds ratio (aOR]: 2.30, 95% confidence interval (CI]: 1.27–4.17), currently employed (aOR: 1.79, 95% CI: 1.03–3.10), and reporting IPV (aOR: 3.61, 95% CI: 1.43–9.10). Having children was marginally associated with HIV testing (aOR: 2.17, 95% CI: 0.98–4.81, p = 0.052). Conclusions: Findings demonstrate suboptimal HIV testing and the importance of tailored strategies to reach urban refugee youth who are unemployed and have limited formal education. There is a need to meaningfully engage urban refugee youth to create enabling environments for sexual health.